Where is the Faith?: Using a CBPR Approach to Propose Adaptations to an Evidence-Based HIV Prevention Intervention for Adolescents in African American Faith Settings - Lightfoot, Alexandra F. (Journal of religion and health, 2014)
African American adolescents are at increased risk for HIV/AIDS. Using a community-based participatory research approach, we engaged three black churches in adapting an evidence-based HIV prevention intervention, Focus on Youth (FOY)+ImPACT, for faith settings. To identify potential adaptations to increase FOY's relevance, utility, and efficacy for faith settings, we conducted eight focus groups pre- and post-intervention. Recommendations for maintaining FOY's core elements and enhancing its cultural authenticity include the following: incorporating faith tools, building pastor capacity, strengthening parent-child communication skills, and expanding social support for parents and youth. Engaging faith communities in adapting and implementing evidence-based HIV prevention programs could reduce HIV/AIDS disparities.